PELATIHAN PENYUSUNAN LAPORAN KEUANGAN BERBASIS AKUNTANSI LINGKUNGAN PADA UKM DI KOTA DAN KABUPATEN BOGOR - Heri Susanto; Eha Hasni Wahidhani; Isbandriyati Mutmainah; Iis Anisa Yulia; Feni Marnilin; Faizal Maad (Jurnal Abdi Inovatif : Pengabdian kepada Masyarakat, 2022)
Abstract Community service is one of the three activities of the Tri Dharma of Higher Education which in its implementation involves all the academic community of higher education. In 2021, the Lecturer Team of the Faculty of Economics and Business will hold Community Service activities with the theme of Training in the preparation of environmental accounting-based financial reports for SMEs (Small and Medium Enterprises) in the City and Regency of Bogor. This theme is important considering that there are externalities from the company's business activities that have not been fully understood, known and responded to by business actors, especially SMEs. Community service activities are carried out with three methods, namely counseling, training, and making simple accounting applications for the preparation of environmental accounting-based financial reports that can be used by business actors who become community service suggestions. Based on the information obtained during the training, it was known that SME participants have not implemented environmental accounting-based financial reports in their business activities, so their understanding of the importance of environmental accounting and its application is very limited. Participants were very enthusiastic because the training could open their horizons and thoughts about good and correct bookkeeping. SME participants are expected to be able to compile financial reports even though they are still in a simple form. In addition, SMEs are more concerned about the environment both internally and externally and can choose raw materials for production and products that are environmentally friendly. AbstrakPengabdian pada masyarakat merupakan salah satu dari tiga kegiatan Tri Dharma Perguruan Tinggi yang dalam pelaksanaannya melibatkan semua civitas akademika perguruan tinggi. Tahun 2021, Tim Dosen Fakultas Ekonomi dan Bisnis menyelenggarakan kegiatan Pengabdian pada Masyarakat dengan tema Pelatihan penyusunan laporan keuangan berbasis akuntansi lingkungan pada UKM (Usaha Kecil dan Menengah) di Kota dan Kabupaten Bogor. Tema ini penting mengingat adanya eksternalitas dari kegiatan bisnis perusahaan yang belum sepenuhnya dipahami, diketahui dan direspon oleh para pelaku usaha khususnya UKM. Kegiatan pengabdian masyarakat dilaksanakan dengan tiga metode, yaitu penyuluhan, pelatihan, dan pembuatan aplikasi akuntansi sederhana untuk penyusunan laporan keuangan berbasis akuntansi lingkungan yang dapat digunakan oleh pelaku usaha yang menjadi saran pengabdian masyarakat. Berdasarkan informasi yang diperoleh saat pelatihan, diketahui bahwa peserta UKM belum menerapkan laporan keuangan berbasis akuntansi lingkungan dalam kegiatan usahanya, sehingga pemahaman tentang pentingnya akuntansi lingkungan dan penerapannya sangat terbatas. Peserta sangat antusias karena pelatihan tersebut dapat membuka wawasan dan pemikiran mereka mengenai pembukuan yang baik dan benar. Peserta UKM diharapkan dapat menyusun laporan keuangan walaupun masih dalam bentuk sederhana. Selain itu pelaku UKM lebih peduli terhadap lingkungan baik internal maupun eksternal serta dapat memilih bahan baku untuk produksi dan produk yang ramah lingkungan.